Fadli Zon dan Politik Identitas dalam Pernyataan Kontroversial tentang Tragedi Pemerkosaan Massal Mei 1998 - Artyson Firman Poyoh; Emha Rifaq Alhaqi; M. Rayhan Nova Ramadhan (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
Minister of Culture Fadli Zon's controversial statement, casting doubt on the existence of mass rape in the May 1998 Tragedy, sparked a strong public reaction, particularly from victims and human rights activists. This study aims to analyze Fadli Zon's statement as a form of identity politics in the context of contemporary Indonesian politics. This research uses a descriptive qualitative method with a discourse analysis approach to public statements, media coverage, and official documents such as reports from the National Commission on Violence Against Women and the Joint Fact-Finding Team (TGPF). The results show that Fadli Zon's statement is not merely a personal view, but rather a representation of identity politics that has the potential to obscure historical truth and reinforce social polarization. The identity politics that emerged in this discourse demonstrates how political power can influence the construction of national history and marginalize minority groups, particularly Chinese women victims of sexual violence. This study emphasizes the importance of historical honesty and the moral responsibility of political elites in preserving the nation's collective memory.